Pancasila sebagai Entitas dan Identitas Bangsa Indonesia dan perwujudan Profil Pelajar Pancasila pada Pendidikan yang Berpihak pada Peserta Didik dalam Pendidikan Abad ke-21 di Ekosistem Sekolah Dasar - SETIAWAN, TRI; Putri , Tresya Adila; Stevie Yolanda; Prakoso, Rangga Hasian; Rita, Putu (LPPM Universitas Terbuka, 2024)
In order to achieve the goals of national education, the Indonesian government has established the Merdeka Curriculum as the current curriculum in place. The Pancasila Student Profile is part of the Merdeka Curriculum designed to meet Indonesia's education targets as a producer of young generations with Pancasila values. This research adopts a descriptive qualitative approach aimed at depicting diverse conditions in actual research. Data collection techniques in qualitative research include observation, interviews, and documentation. The research findings indicate that Pancasila plays a central role in shaping the identity and character of the Indonesian nation. As the foundation of the state, Pancasila reflects the diversity of values and characteristics of the Indonesian nation. The concept of Pancasila Students emphasizes the importance of education in shaping individuals who are skilled, morally upright, globally diverse, cooperative, independent, critical thinkers, and creative. The implementation of the Pancasila Student Profile at SDN 58/IV Kota Jambi has been successful, demonstrating a commitment to shaping the younger generation who firmly uphold Pancasila values for the nation's progress.